Molecular analyses detect natural coinfection of water buffaloes (Bubalus bubalis) with bovine viral diarrhea viruses (BVDV) in serologically negative animals = Detección molecular de coinfección con los virus de la diarrea viral bovina (BVDV) en búfalos de agua (Bubalus bubalis) serológicamente negativos - Craig, María Isabel (2015)
Infection of water buffaloes (Bubalus bubalis) with bovine viral diarrhea viruses (BVDV) has been confirmed in several studies by serological and molecular techniques. In order to determine the presence of persistently infected animals and circulating species and subtypes of BVDV we conducted this study on a buffalo herd, whose habitat was shared with bovine cattle (Bossp.). Our serological results showed a high level of positivity for BVDV-1 and BVDV-2 within the buffalo herd. The molecular analyses of blood samples in serologically negative animals revealed the presence of viral nucleic acid, confirming the existence of persistent infection in the buffaloes. Cloning and sequencing of the 5′ UTR of some of these samples revealed the presence of naturally mix-infected buffaloes with at least two different subtypes (1a and 1b), and also with both BVDV species (BVDV-1 and BVDV-2).